PERFORMANCE MANAGEMENT EVALUATION BASED ON ACCREDITATION RESULTS AT STTBI BY HIGHER NATIONAL EDUCATION ASSOCIATION (BALANCED SCORECARD APPROACH) - FRANKY, FRANKY (Jurnal Ilmiah Educational Management, 2016)
The objective of this research was to understand comprehensively the performance management evaluation of STTBI. The research itself use the national standards for the higher education evaluation, such as vision and strategy standard; leadership and total quality management standard; outcomes quality standard; human resources standard; curriculum and academic environment standard; funding, some supports, and information system standard; finally, research, community responsibility, and cooperation standard. The researcher used one method evaluation to value the performance management of STTBI through to translation the standards above to some perspectives in balanced scorecard. The balanced scorecard contains some perspectives such as vision and strategy, financial, customer, internal business process, and learning and growth perspective. The approach of this research uses goal oriented based or objectives oriented approach and qualitative method used as well. The conclusions and recommendation such as STTBI have to do the re-formulate the vision statement in order to focus the organization purpose; all activities sort of the student enrollment, financial, recruitment policy, and etc. must be documented in standard operational procedures; in the business process internal will be divided by five criteria such as design, develop, maintain, and regulation; STTBI has to update and upgrade the human resource recruitment system in order to find and get the best person (lecturer); and to make a balance in the sustainability in finance, the STTBI has to open to find other strategic business unit opportunity.